Identification and susceptibility of clinical isolates of Candida spp. to killer toxins - Robledo Leal, Efrén Ricardo; Rivera Morales, Lydia Guadalupe; Sangorrín, M. P.; González González, Gloria María; Ramos Alfano, Gerardo; Adame Rodríguez, Juan Manuel; Alcocer González, Juan Manuel; Aréchiga Carvajal, Elva Teresa; Rodríguez Padilla, Cristina (2018)
Abstract Although invasive infections and mortality caused by Candida species are increasing among compromised patients, resistance to common antifungal agents is also an increasing problem. We analyzed 60 yeasts isolated from patients with invasive candidiasis using a PCR/RFLP strategy based on the internal transcribed spacer (ITS2) region to identify different Candida pathogenic species. PCR analysis was performed from genomic DNA with a primer pair of the ITS2‑5.8S rDNA region. PCR‑positive samples were characterized by RFLP. Restriction resulted in 23 isolates identified as C. albicans using AlwI, 24 isolates as C. parapsilosis using RsaI, and 13 as C. tropicalis using XmaI. Then, a group of all isolates were evaluated for their susceptibility to a panel of previously described killer yeasts, resulting in 75% being susceptible to at least one killer yeast while the remaining were not inhibited by any strain. C. albicans was the most susceptible group while C. tropicalis had the fewest inhibitions. No species‑specific pattern of inhibition was obtained with this panel of killer yeasts. Metschnikowia pulcherrima, Pichia kluyveri and Wickerhamomyces anomalus were the strains that inhibited the most isolates of Candida spp.